Relationship Between Nomophobia and Internet Addiction with Aggressive Behavior in Class VII and VIII Students of MTs Antasari Martapura - Mashita Listiyarini; Nina Permata Sari; Akhmad Sugianto (The Innovation of Social Studies Journal, 2023)
Some students of MTs Antasari Martapura tend to aggressive behavior caused by the high intensity of smartphones and the internet. High use of smartphones and the internet can affect an individual psychologically, triggering aggressive behavior in the individual. This study aims to determine the relationship between nomophobia and internet addiction with aggressive behavior in class VII & VIII students at MTs Antasari Martapura. This study uses a quantitative approach with the type of correlation research. The sampling technique used purposive sampling. This research was conducted on students of class VII & VIII MTs Antasari Martapura with a population of 110 students and obtained a sample of 86 people. Data analysis techniques used descriptive statistics, rank spearmen correlation, and multiple regression. As for the results of the study, there is no relationship between the variable nomophobia (X1) and internet addiction (X2) with aggressive behavior (Y) in class VII and VIII students at MTs Antasari Martapura because it can be seen in the significance value for the relationship between nomophobia (X1) and addiction. Internet (X2) with aggressive behavior (Y) is 0.154 > 0.05, and the calculated F value is 1.912 < 3.11. This means that the variables of nomophobia and internet addiction with aggressive behavior do not have a relationship because the significance value of the three variables is > 0.05, and the calculated F value is < 3.11. So (Ho) can be accepted that there is no relationship between the variables of nomophobia and internet addiction with aggressive behavior. Suggestions for students are expected to be able to control the use of smartphones and the internet wisely and adequately in order to avoid these two mental disorders. Furthermore, students can control the level of emotion and behavior that is issued so as not to trigger a tendency to aggressive behavior.